Sistem Informasi Manajemen Hubungan Pelanggan pada PT Quinsha Trans Jaya - Muhammad Rafliansyah; Yulistia Yulistia; Chriestina Chriestina (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
Increasingly fierce business competition forces companies to look for innovations and strategies to maintain customer satisfaction and trust. PT Quinsha Trans Jaya, a tourism transportation services company, faced problems in providing service information and collecting customer feedback. To overcome this, a website-based customer relationship management system is needed. This system is expected to improve operational performance, facilitate purchases, and provide complete information to customers. The development of the system uses the Rational Unified Process (RUP) method and aims to help PT Quinsha Trans Jaya retain and attract new customers. The customer relationship management information system built will focus on service transactions through the website. Then this system has information features related to rentals and purchases as well as available promotions. There is also a reward feature, feedback from customers that helps companies increase customer loyalty.